(untitled) (Abstracta, 2024)
Artigos publicados 2023 - P322-2023 à P385-2023 Eventos publicados 2023 - P386-2023 à P387-2023 Meeting abstract 2023 - Me001-2023 Artigos publicados 2024 - P001-2024 à P016-2024 Defesas de Dissertações do IFGW - D001-2024 à D006-2024 Defesas de Teses do IFGW - T001-2024 à T003-2024 Defesas do PECIM - P001-2024